Would you prefer a set menu or à la carte? An empirical study of multiple services and choices of consumer in the Swedish telecommunications market - Pratompong Srinuan; Chalita Srinuan; Erik Bohlin (International Telecommunications Society (ITS), 2011)
Received analyses state that firms can use a bundling strategy to retain customers and capture new customers. Factors that determine the bundling strategy include product discount, service provider and customer characteristics. Consequently, this study addresses the fundamental question: What are the key determining factors that explain the probability that a consumer will buy multiple services? A Poisson regression model is employed to examine whether the product discount, service provider, socio-economic variables and geographical location impact on consumer decisions. Data from a national survey in 2009 commissioned by Post-och Telestyrelsen, the Swedish telecommunications regulator, are analysed. The results clearly show that the discount, service provider and income of the consumer affect the consumer's buying decision. For example, a consumer who receives a discount or has a high income is more likely to buy a bundle service (set menu) or select more services from the current service provider into his basket than a consumer who buys an individual service (à la carte). Service providers, cable TV operators and telecommunications carriers can also lock-in their consumer and expand their market position from one particular service to another using bundle services. Thus, this may be the time for the telecommunications regulator to consider the market definition.
Keywords: 330